A review on global solar energy policy - Solangi, K.H.; Islam, M.R.; Saidur, Rahman; Rahim, N.A.; Fayaz, H. (Elsevier, 2011)
To overcome the negative impacts on the environment and other problems associated with fossil fuels have forced many countries to inquire into and change to environmental friendly alternatives that are renewable to sustain the increasing energy demand. Solar energy is one of the best renewable energy sources with least negative impacts on the environment. Different countries have formulated solar energy policies to reducing dependence on fossil fuel and increasing domestic energy production by solar energy. This paper discusses a review about the different solar energy policies implemented on the different countries of the world. According to the 2010 BP Statistical Energy Survey, the world cumulative installed solar energy capacity was 22928.9 MW in 2009, a change of 46.9 compared to 2008. Also this paper discussed the existing successful solar energy policies of few selected countries. Based on literatures, it has been found that FIT, RPS and incentives are the most beneficial energy policies implemented by many countries around the world. These policies provide significant motivation and interest for the development and use of renewable energy technologies. Also the status of solar energy policy for Malaysia is investigated and compared with that of the successful countries in the world.